Seed Dispersal: Theory and its Application in a Changing World - Dennis, Andrew J (CABI, 2014)
The process of seed dispersal frequently begins with a fruit interacting with a frugivore, and this interaction is a fitting place to begin a book on seed dispersal. The interactions between animals, fruits and their seeds dominate plant reproduction in most habitats. Although we often think of tropical forests, even many desert plants produce fleshy fruit designed to attract animal dispersers, and these plants are frequently abundant species (see Bronstein et al., Chapter 7). Of all the potential vectors for dispersing seeds, animals are the most susceptible to disturbance by humans (see Part IV), making it essential that the process of seed dispersal mediated by animals is understood to the fullest possible extent in our rapidly changing world.